Ambiguitas dan Inkonsistensi Kedudukan serta Kewenangan Wakil Kepala Daerah dalam Sistem Pemerintahan Daerah - Syafri Hariansah; Rio Armanda Agustian (PROGRESIF: Jurnal Hukum, 2022)
This research is addressed to theoretically examine authority and position of deputy head of region in local government system in the post-reform time, in particular by using Philipus M Hadjon's authoritative theory as an analytical tool. We apply normative juridical approach through analysis of theory, concepts, legal principles as well as law and regulation which have correlation with this research. Our result shows that the authority of the deputy head can be achieved in three different ways: first, direct or explicit power governed by the law, second and third through delegation and mandate from higher authority (e.g. regional head), respectively. Interestingly, we notice that most of the tasks are unfortunately mostly in assisting mode, while we argue that this can be also carried out by local secretary. This power overlapping could actually create ambiguity and further have implication in the urgency of deputy head position in the regional government system.